Expansion of Fcγ Receptor IIIa–Positive Macrophages, Ficolin 1–Positive Monocyte‐Derived Dendritic Cells, and Plasmacytoid Dendritic Cells Associated With Severe Skin Disease in Systemic Sclerosis - Xue, Dan; Tabib, Tracy; Morse, Christina; Yang, Yi; Domsic, Robyn T.; Khanna, Dinesh; Lafyatis, Robert (Arthritis & rheumatology (Hoboken, N.J.), 2022)
Objective In this study, we sought a comprehensive understanding of myeloid cell types driving fibrosis in diffuse cutaneous systemic sclerosis (dcSSc) skin. Methods We analyzed the transcriptomes of 2,465 myeloid cells from skin biopsy specimens from 12 dcSSc patients and 10 healthy control subjects using single‐cell RNA sequencing. Monocyte‐derived dendritic cells (mo‐DCs) were assessed using immunohistochemical staining and immunofluorescence analyses targeting ficolin‐1 (FCN‐1). Results A t‐distributed stochastic neighbor embedding analysis of single‐cell transcriptome data revealed 12 myeloid cell clusters, 9 of which paralleled previously described healthy control macrophage/DC clusters, and 3 of which were dcSSc‐specific myeloid cell clusters. One SSc‐associated macrophage cluster, highly expressing Fcγ receptor IIIA, was suggested on pseudotime analysis to be derived from normal CCR1+ and MARCO+ macrophages. A second SSc‐associated myeloid population highly expressed monocyte markers FCN‐1, epiregulin, S100A8, and S100A9, but was closely related to type 2 conventional DCs on pseudotime analysis and identified as mo‐DCs. Mo‐DCs were associated with more severe skin disease. Proliferating macrophages and plasmacytoid DCs were detected almost exclusively in dcSSc skin, the latter clustering with B cells and apparently derived from lymphoid progenitors. Conclusion Transcriptional signatures in these and other myeloid populations indicate innate immune system activation, possibly through Toll‐like receptors and highly up‐regulated chemokines. However, the appearance and activation of myeloid cells varies between patients, indicating potential differences in the underlying pathogenesis and/or temporal disease activity in dcSSc.